2010
DOI: 10.1088/1751-8113/43/47/474029
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz tails for alloy-type models in a constant magnetic field

Abstract: Dedicated to the memory of Pierre Duclos.Abstract. In this paper, we study Lifshitz tails for a 2D Landau Hamiltonian perturbed by a random alloy-type potential constructed with single site potentials decaying at least at a Gaussian speed. We prove that, if the Landau level stays preserved as a band edge for the perturbed Hamiltonian, at the Landau levels, the integrated density of states has a Lifshitz behavior of the type e − log 2 |E−2bq| .Résumé. Dans cette note, nous démontrons qu'en dimension 2, la densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…IV, where we compare the results with the results in Ref. 19. We then investigate the energy dependence on the collapse of the axes within the framework of Palmer and study the trion wave functions and their dependence on the dimension of the system.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…IV, where we compare the results with the results in Ref. 19. We then investigate the energy dependence on the collapse of the axes within the framework of Palmer and study the trion wave functions and their dependence on the dimension of the system.…”
Section: Introductionmentioning
confidence: 78%
“…We found that the fractional D dimensional model provided accurate predictions of the trion binding energy on the surface of a cylinder. 19,20 Other authors have demonstrated that this model also predicts exciton binding energies in quantum wells and carbon nanotubes very accurately. [12][13][14][15][16]21 Thus, the model is applicable to a wide variety of systems.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The behaviour (1.9) is known as Lifshitz tails (for more details, see part IV.9.A of [19]) and the exponent −d/2 is called the Lifshitz exponent of the operator. The principal results known on Lifshitz tails are mainly shown for Schrödinger operators, in both continuous and discrete cases (see [7,8,11,14,18,22] and others) and for Schrödinger operators with magnetic fields (see [12,15] ).…”
Section: A Particular Modelmentioning
confidence: 99%
“…See [33,40,44,53,63], etc. for random alloy-type models, [2,12,13,19,20,27,38,43,51,70], etc. for random Landau Hamiltonians and [42,57], etc.…”
Section: Introductionmentioning
confidence: 99%